Principles of modern radar. Volume III, - Melvin, William L. (SciTech Publishing, 2014)
Principles of Modern Radar: Radar Applications is the third of the three-volume seriesof what was originally designed to be accomplished in one volume. As the final volumeof the set, it finishes the original vision of a complete yet bounded reference for radartechnology. This volume describes fifteen different system applications or class ofapplications in more detail than can be found in Volumes I or II. As different as the applications described, there is a difference in how these topicsare treated by the authors. Whereas in Volumes I and II there is strict adherence tochapter format and leve.